Nephrotoxicity of uranium in drinking water from private drilled wells - Seldén, Anders I.; Lundholm, Cecilia; Edlund, Bror; Högdahl, Camilla; Ek, Britt-Marie; Bergström, Bernt E.; Ohlson, Carl-Göran (Environmental research, 2009)
To investigate the association between uranium in drinking water from drilled wells and aspects of kidney function measured by sensitive urine tests. Three hundred and one of 398 eligible subjects (75.6%) aged 18–74 years with daily drinking water supplies from private drilled wells located in uranium-rich bedrock (exposed group) volunteered to participate along with 153 of 271 local controls (56.4%) who used municipal water. Participants responded to a questionnaire on their water consumption and general health, and provided a morning urine sample and drinking water for analysis. The uranium content of well water samples (n=153) varied considerably (range <0.20–470μg/l, median 6.7μg/l, 5% >100μg/l), while uranium levels in all samples of municipal water (n=14) were below the limit of quantification (0.2μg/l). Urinary levels of uranium were more than eight times higher in exposed subjects than in controls (geometric means 38 and 4.3ng/l, respectively; p<0.001), but their mean urine lead levels were not significantly different. There was a strong curvilinear correlation between uranium in drinking water and in urine (r2=0.66). Levels of albumin, β2-microglobulin, protein HC as well as kappa and lambda immunoglobulin chains in urine from exposed and controls were similar. The N-acetyl-β-d-glucosaminidase (NAG) activity was significantly lower in the exposed group vs. controls, possibly secondary to differential storage duration of samples from the two groups. Even in regression models adjusting for gender, age and smoking no association of uranium in water and the kidney function parameters was observed. Using uranium in urine in the entire study group as a marker of exposure, however, a tendency of exposure-related increases of β2-microglobulin, protein HC and kappa chains were noted. This tendency was enhanced after exclusion of subjects with diabetes mellitus from the analysis. Uranium levels in urine were strongly correlated to levels in drinking water from drilled wells. There were no clear signs of nephrotoxicity from uranium in drinking water at levels recorded in this study, but some indications of an effect were observed using uranium in urine as a measure of overall uranium exposure. The clinical relevance of these findings remains unclear.